Executive functions and classroom behaviour in second graders - Heemskerk, Christina Hubertina Helena Maria; Roebers, Claudia M. (Frontiers in Education, 2023)
Background Executive functions along with on-task behaviour in the classroom relate to academic success. Examining the shared and non-shared variances in their relationships with academic achievement may lead to a better understanding of the contribution of executive functions to achievement and may uncover a mechanism to explain why they are so important for school success. Specifically, we investigated the extent to which executive functions and classroom behaviour offer different and similar perspectives on children’s self-regulatory behaviour, and make unique contributions to academic achievement. Method Data were collected from 129 2nd grade students (M age = 7.93 years, SD = 0.5; 44.2% female). Participants were observed for 25 minutes during a ‘business-as-usual’ classroom lesson, following a momentary assessment protocol; we developed and used an openly available mobile application. Subsequently, participants completed an executive function task (Hearts and Flowers) in small groups on tablet computers. Teachers rated students’ academic achievement in language and mathematics. Results We found unique contributions for on-task behaviour and executive functions to academic achievement in 2nd grade. Moreover, we found that 27-31% of the total effect of inhibition on language achievement was mediated through on-task behaviour. Conclusion We have shown that executive functions and on-task behaviour share variance in their relationship to academic achievement, as well as providing a unique perspective on children’s self-regulatory behaviour. Thus, researchers might want consider the inclusion of both executive function tasks and ecologically valid measures such as the current, easy to apply behavioural observation in a naturalistic setting in their future work.